Decrease in water clarity of the southern and central North Sea during the 20th century. (6th March 2015) - Capuzzo, Elisa; Stephens, David; Silva, Tiago; Barry, Jon; Forster, Rodney M.
Abstract Light in the marine environment is a key environmental variable coupling physics to marine biogeochemistry and ecology. Weak light penetration reduces light available for photosynthesis, changing energy fluxes through the marine food web. Based on published and unpublished data, this study shows that the central and southern North Sea has become significantly less clear over the second half of the 20th century. In particular, in the different regions and seasons investigated, the average Secchi depth pre‐1950 decreased between 25% and 75% compared to the average Secchi depth post‐1950. Consequently, in summer pre‐1950, most (74%) of the sea floor in the permanently mixed area off East Anglia was within the photic zone. For the last 25+ years, changes in water clarity were more likely driven by an increase in the concentration of suspended sediments, rather than phytoplankton. We suggest that a combination of causes have contributed to this increase in suspended sediments such as changes in sea‐bed communities and in weather patterns, decreased sink of sediments in estuaries, and increased coastal erosion. A predicted future increase in storminess (Beniston et al., 2007; Kovats et al., 2014) could enhance the concentration of suspended sediments in the water column and consequently lead to a further decrease in clarity, with potential impacts on phytoplankton production, CO2 fluxes, and fishery production.